PERCEIVED COUNSELLING STRATEGIES FOR THE PREVENTION OF HUMAN IMMUNE VIRUS (HIV) AMONG ADOLESCENTS IN ONITSHA EDUCATION ZONE (Journal of Guidance and Counselling Studies, 2020)
The study determined the counselling strategies for the prevention of Human Immune Virus (HIV) among adolescents in Onitsha Education Zone of Anambra State. A descriptive survey research design was adopted for the study. There are 32 public secondary schools in Onitsha education zone, therefore the population for the study comprised of the 32 counsellors from the education Zone.The population was small and therefore there was no sampling. The entire population was used as the sample size. The instrument for the study is researchers’ constructed questionnaire, titled counselling strategies for preventing the spread of HIV among adolescents questionnaire and two experts validated the instrument. Three research questions were posed and a decision rule of 2.5 was used as a criterion value to guide the study. The data collected was analyzed using mean. The items were based on 4 point rating.Based on the mean scores, the following findings were obtained. Organization of seminars for the students on periodic basis, individual counselling and the use of peer education are effective measures for preventing the spread of HIV. Based on the findings, conclusion was drawn, implications highlighted and recommendations made to include that counsellors should mount enlightenment programs from time to time through conferences, workshops on the issue of HIV among other recommendations.
Keywords: Counselling; Strategies; Human Immune Virus; Adolescents